Effect of hematite nanofiller on the attenuation of PTFE/Fe2O3 nanocomposites at microwave frequency - Alhaji, Bello Murtala; Azis, Raba’ah Syahidah; Shabdin, Muhammad Kashfi; Osman, Nurul Huda; Yakubu, Abubakar (Malaysian Solid State Science and Technology Society, 2023)
The use of nanocomposites in microwave applications has received considerable attention because of their exceptional electromagnetic properties. This study investigates the effect of incorporating hematite (Fe2O3) nanofillers on the attenuation properties of polytetrafluoroethylene (PTFE)/Fe2O3 nanocomposites at microwave frequencies. The nanocomposites were prepared by dispersing hematite nanoparticles of 5, 7.5, 10, 12.5, and 15 within a PTFE matrix using the dry mixing method. The fabricated nanocomposites were characterized for their morphological and electromagnetic properties. The results showed a uniform dispersion of hematite nanoparticles within the PTFE matrix which was confirmed by field emission scanning electron microscopy (FESEM). The attenuation of the PTFE/Fe2O3 nanocomposite substrate with varying percentages of Fe2O3 nanofiller was determined using the rectangular waveguide (RWG) method. The measurement involved analyzing the magnitudes of the transmission coefficient (S21) obtained from the waveguide. The results indicated that as the content of Fe2O3 nanofiller was increased, the attenuation also increased. The composite with 15 PTFE/Fe2O3 exhibited the highest attenuation with a magnitude of 14.09 dB, while the composite with 5 Fe2O3 nanofiller showed the lowest attenuation with a magnitude of 12.40 dB. These findings offer valuable insights for the development of PTFE/Fe2O3 nanocomposites in applications requiring effective microwave attenuation, such as electromagnetic shielding and absorption devices.